Common Heritage of Mankind Principle Under UNCLOS 1982: Attempt to Prevent Neo-Colonialism? - Agustina Merdekawati; Irkham Afnan Trisandi Hasibuan (Yuridika, 2026)
The United Nations Convention on the Law of the Sea (UNCLOS) 1982 adopted the Common Heritage of Mankind principle to regulate deep seabed mining beyond national jurisdictions, known as the Area. The push to establish this regulation materialized when the international community faced rapid economic globalization, which opened the opportunity for the emergence of neo-colonialism through the utilization monopoly in the Area by a select few developed countries. This research aimed to examine the extent to which the adoption of the Common Heritage of Mankind principle correlates with the effort to prevent the neo-colonialism practice in the context of growing economic globalization. The answer to this question is necessary to understand the law of the sea regime. This normative research utilized secondary data to support the conclusion, gathered through a literature study. The results show that there is a positive correlation between the adoption of the Common Heritage of Mankind principle and the prevention of neo-colonialism in the utilization of Area. The study found that the principle has prevented the emergence of neo-colonialism by recognizing the resources as belonging to mankind, which makes the factors of capital ownership and technological capabilities of individual countries irrelevant when it comes to accessing the benefits derived from the Area.